Rat cellular retinol-binding protein II: use of a cloned cDNA to define its primary structure, tissue-specific expression, and developmental regulation. - Li, E (1986)
The primary structure of rat cellular retinol-binding protein (CRBP) II has been determined from a cloned cDNA. Alignment of this 134-amino acid, 15,580-Da polypeptide with rat CRBP revealed that 75 of 133 comparable residues are identical. Both proteins contain four tryptophan residues, which occupy identical relative positions in the two primary structures, providing a structural explanation for their similar fluorescence spectra when complexed to retinol. Two of the three cysteines in each single-chain protein are comparably positioned. Both polypeptides contain reactive thiol groups, but the rate of disruption of CRBP II-retinol complexes by p-chloromercuribenzoate is greater than that of CRBP-retinol. The small intestine contains the highest concentrations of CRBP II mRNA in adult rats. CRBP II mRNA is first detectable in intestinal RNA during the 19th day of gestation, a time that corresponds to the appearance of an absorptive columnar epithelium. Unlike in intestine, a dramatic fall in liver CRBP II mRNA concentration occurs immediately after birth. The CRBP II gene remains quiescent in the liver during subsequent postnatal development. These data suggest that ligand-protein interactions may be somewhat different for the two rat CRBPs. They also support the concept that CRBP II plays a role in the intestinal absorption or esterification of retinol and suggest that changes in hepatic metabolism of vitamin A occur during development.